How is visual separation assessed? By counting distance units - Dopkins, Stephen (Frontiers in Psychology, 2024)
How does the human visual system assess the separation between pairs of stimuli in a frontal plane? According to the direct (or subtractive) view the system finds the difference between the positions of the stimuli in a localization system. According to the indirect (or additive) view the system finds the number of instances of a distance unit lying between representations of the stimuli. Critically, position is explicitly represented under the direct view, with separation being derived from position. Position is not explicitly represented under the indirect view; separation is consequently inferred by counting an internal unit of distance. Recent results favor the indirect over the direct view of separation assessment. Dissociations between assessments of separation and position, various context effects in the assessment of separation, and suggestions that position information is not cleanly accessed argue against the direct view. At the same time, various context effects in separation assessment argue for the indirect view. Recent findings regarding the brain bases of vision are consistent with the indirect view. In short, recent results suggest that assessing the separation between two frontal stimuli involves integrating distance units between representations of the stimuli.